Pengaruh Proses Freeze-Drying terhadap Viabilitas Streptococcus agalactiae pada Media Chitosan, Skim Milk, dan Media Kultur BHIB - Aranty Fahira Ardisa; N Nafiqoh; TH Kurniati (Seminar Nasional Lahan Suboptimal, 2021)
Ardisa FA, Nafiqoh N, Kurniati TH. 2021. The effect of the freeze-drying process on viability  streptococcus agalactiae on chitosan media, skim milk, and BHIB culture media. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 296-304.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Streptococcus agalactiae bacteria are cocci-shaped bacteria, gram positive, catalase (-) and are pathogenic that can attack fish. One of the alternative to overcome the attack of pathogenic bacteria is by giving vaccines to fish. Vaccines can be made using the freeze-drying technique, which has the advantage of maintaining the quality of the drying results. This study aims to determine the technique of making S. agalactiae vaccines by freeze-drying on encapsulation media and to determine the viability of S. agalactiae on skim milk, chitosan and BHIB (Brain Heart Infusion Broth) culture media. The stages of making the freeze-dried vaccines include confirmation of S. agalactiae bacteria through Gram staining, catalase enzyme test, and detection of virulence factor genes based on cps L, cps J, and cps G genes. The vaccine was made using the freeze dryer method on chitosan encapsulation media, skimmed milk, and BHIB. The viability of bacteria in vaccine preparations was known based on the calculation of the total plate number. The test results showed the isolates were gram positive, coccus-shaped and catalase negative. The isolates were also confirmed to have cps L, cps J, and cps G genes. After 24 hours the total bacterial plate count in skim milk and chitosan medium was 8x1012 CFU/ml and 3.2x1012 CFU/ml, while in BHIB medium the number of colonies exceeds the calculation standard limit. Based on these results, the three tested media have potential as encapsulation media for S. agalactiae vaccine production.